IMPROVING THE EFFICIENCY OF PEDAGOGICAL EDUCATION AS THE MOST IMPORTANT FACTOR IN THE DEVELOPMENT OF SOCIETY (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem concerning the ways of improvement pedagogical education effectiveness.
Keywords: pedagogical education; educational process; modernization of higher education